Features of harvesting machinery operation on weak soils in the Far East Region - A. N. Panasyuk; Z. A. Godzhaev; M. V. Kandelya; A. V. Lipkan'; V. M. Shiryaev; V. A. Kuz'min (Сельскохозяйственные машины и технологии)
The authors based on own researches established actual problems of harvesting in the Amur region: ensuring passability of machines on the waterlogged soil, need of machines adaptivising to technologies of soybean harvesting, transfer of a part of the combine fleet to a caterpillar track, implementation of reloading reducing impact on the soil technologies of harvesting, increase in cost efficiency of mashines use and postharvest drying of grain and corn.Perspective solutions of problems are shown: design development of caterpillar end trucks of combines with the rubber-reinforced tracks (RRT); engineering and production of the soybean-grain harvester with RRT or a set of devices for the grain harvester with RRT as the option transferring it to the category the soybean-grain ones; process development to provide harvesting of soybean heap by the machine with RRT which crush and spread straw across the field simultaneous, to deliver soybean heap to stationary point of postharvest handling for the subsequent separation into seeds, marketable soybean and a soy chaff as valuable protein feed for livestock production, ready for feeding and storage; engineering of the forage harvester with RRT on a block and modular basis, that is based on the multipurpose power mean on RRT with the 4-machine scheme of a hydrostatic power drive of a undercarriager; development of a design of caterpillar blocks with triangular shape of contour; implementation of reloading technologies of harvest operations on system VIMLIFT.Production of harvest transport vehicles should be performed on a block and modular basis - in the form of a complex of self-propelled agricultural machines based on the released multipurpose power module with a set of the replaceable technological adapters providing its loading within a year. The agroterm of corn on grain harvesting should be delayed to later time when grain reaches standard humidity naturally.